IDENTIFIKASI PENCAHAYAAN ALAMI GEDUNG SEKOLAH MUHAMMADIYAH AMBON BERDASARKAN SNI 03-6197-2000 - Jeams Huwae; Fauzan .A. Sangadji; Felix Taihuttu (JURNAL SIMETRIK, 2026)
This study aims to evaluate the levels of natural and artificial lighting in the Muhammadiyah School Ambon building based on SNI 03-6197-2000. The research was conducted in 15 rooms, including classrooms and supporting spaces, using a descriptive quantitative method with direct measurements obtained through a lux meter.The results indicate that all rooms have lighting levels below the minimum standard requirement of 250 lux for classrooms. Inadequate lighting is caused by limited window openings, obstructed room positions, and building designs that do not support optimal daylight penetration, combined with insufficient artificial lighting conditions.This study concludes that the lighting system at Muhammadiyah School Ambon does not meet visual comfort standards. Improvements to artificial lighting, optimization of natural lighting, and regular maintenance of lighting installations are recommended to enhance the quality of the learning environment. Keyword:  Lighting School Indonesian National Standard Sni 03-6197-2000, Lux Meter Classroom Visual Evalution